Risk factors associated with 90-day readmissions following odontoid fractures: a nationwide readmissions database study - Glinski, Alexander von; Frieler, Sven; Elia, Christopher; Patchana, Tye; Takayanagi, Ariel; Arvind, Varun; Pierre, Clifford; Ishak, Basem; Chapman, Jens R.; Oskouian, Rod J. (Spine, 2021)
Study Design. - Nationwide Readmissions Database Study. - Objective. - The aim of this study was to investigate readmission rates and factors related to readmission after surgical and nonsurgical management of odontoid fractures. - Summary of Background Data. - Management of odontoid fractures, which are the most common isolated spine fracture in the elderly, continues to be debated. The choice between surgical or nonsurgical treatment has been reported to impact mortality and might influence readmission rates. Hospital readmissions represent a large financial burden upon our healthcare system. Factors surrounding hospital readmissions would benefit from a better understanding of their associated causes to lower health care costs - Methods. - A retrospective study was performed using the 2016 Healthcare Utilization Project (HCUP) Nationwide Readmission Database (NRD). Demographic information and factors associated with readmission were collected. Readmission rates, complications, length of hospital stay were collected. Patients treated operatively, nonoperatively, and patients who were readmitted or not readmitted were compared. Statistical analysis was performed using open source software SciPy (Python v1.3.0) for all analyses. - Results. - We identified 2921 patients who presented with Type II dens fractures from January 1, 2016 to September 30, 2016, 555 of which underwent surgical intervention. The readmission rate in patients who underwent surgery was 16.4% (91/555) and 29.4% (696/2366) in the nonoperative group. Hospital costs for readmitted and nonreadmitted patients were $353,704 and $174,922, and $197,099 and $80,715 for nonoperatively managed patients, respectively. Medicaid and Medicare patients had the highest readmission rate in both groups. Charlson and Elixhauser comorbidity indices were significantly higher in patients who were readmitted (P < 0.0001). - Conclusion. - We report an overall 90-day readmission rate of 16.4% and 29.4%, in operative and nonoperative management of type II odontoid fractures, respectively. In the face of a rising incidence of this fracture in the elderly population, an understanding of the comorbidities and age-related demographics associated with 90-day readmissions following both surgical and nonsurgical treatment are critical. - Level of Evidence: 3